Parameters influencing the photo-induced electron transfer from tryptophan-containing peptides to a RuII complex: a systematic study. (23rd September 2015) - Garnir, Kevin; Estalayo-Adrián, Sandra; Lartia, Rémy; De Winter, Julien; Defrancq, Eric; Surin, Mathieu; Lemaur, Vincent; Gerbaux, Pascal; Moucheron, Cécile
Abstract : Ruthenium(ii ) polyazaaromatic complexes have gained interest in recent decades as biomolecular tools, especially in the development of new phototherapeutic agents. These light emissive Ru complexes based on π-deficient ligands were first designed to allow a photo-induced electron transfer (PET) with the guanine base in DNA since their 3 MLCT state is highly photo-oxidizing. Later the field of research was extended to proteins with the highlighting of a PET process with the tryptophan residue. This paper reports the kinetics of the luminescence quenching of [Ru(TAP)2 phen] 2+ by several selected peptide sequences containing at least one tryptophan residue. By using a peptide library we highlight the important parameters influencing the kinetics of the photo-electron transfer process, such as the net electrostatic charge and the number of tryptophan residues. The best peptide candidates were selected to study the formation of photo-products by MALDI-ToF mass spectrometry. A high photoreactivity of the [Ru(TAP)2 phen] 2+ complex was observed and multiple photoadducts were characterized, among them inter-peptidic adducts as well as intra-peptidic adducts.